Model Pemberdayaan Ekonomi Syariah Berbasis Pesantren di Wilayah Pedesaan Sulawesi Tenggara: Kajian Fenomenologi pada Pondok Modern Darussalam Gontor Kampus 6 - Zulfajrin; Yusril Mahendra; Ziana Asyifa (Islamic Banking and Finance, 2026)
Modern Islamic boarding schools in Indonesia have the potential to serve as instruments for empowering rural communities economically based on sharia values, but this potential is not uniform across all institutional and geographical contexts. This study aims to construct a model of sharia economic empowerment implemented by the Darussalam Gontor Modern Islamic Boarding School, Campus 6, Riyadhatul Mujahidin in Mowila District, South Konawe Regency, Southeast Sulawesi, while also identifying the opportunities and constraints that shape the capacity and reach limits of the model. The study used a qualitative phenomenological approach with 12 key informants. Data were collected through in-depth interviews, participant observation, and document analysis. The results show that the empowerment model in operation encompasses four dimensions: productive economy, internal employment, socio-religious, and basic infrastructure. All economic cooperation is based on the musyarakah contract, which substantively fulfills the principles of Islamic jurisprudence. On the opportunity side, Islamic boarding school regulations (Law No. 18/2019), support for the One Pesantren One Product (OPOP) program, and partnerships with Islamic financial institutions offer significant room for expansion. Conversely, key structural barriers, such as a single-door funding system from the central campus, limited certified human resources, and a geographic reach of only six out of nine villages, indicate that this model is still in a pre-consolidated growth phase.